PROSEDUR PEMERIKSAAN MICTURATING CYSTOURETROGRAPHY (MCU) PEDIATRIK DENGAN KLINIS HIDRONEFROSIS DI INSTALASI RADIOLOGI RUMAH SAKIT UNS - Sanifa Winda Sari; Anshor Nugroho; Ayu Mahanani (Bajang Institute, 2025)
Baground: Micturating Cystourethrography (MCU is a radiological examination performed in pediatric patients using contrast media to assess the function, structure, and abnormalities of the urinary bladder (vesica urinaria) and urethra. The standard MCU technique typically employs AP and RPO post- contrast projections, with contrast media introduced via a catheter or abocath. At UNS Hospital, however, only the AP projection is used, and contrast media is introduced using the drip infusion method. This study aims to examine the MCU examination procedure performed at the Radiology Department of UNS Hospital, specifically focusing on the drip infusion method of contrast administration and the exclusive use of the AP projection. Method: This study employed qualitative descriptive method with case study approach. Data collection was conducted at UNS Hospital between December 2024 and May 2025. The research subjects were three radiographers and one radiology specialist, while the research object was pediatric patients with hydronephrosis. Data were collected through observation, interviews, documentation, and literature review. Data analysis involved data reduction, data presentation, and conclusion drawing.Results: Observations and interviews showed that at UNS Hospital, the procedure is performed using two projections: AP plain film and AP post-contrast. Contrast media is administered using the drip infusion technique with an IV set, allowing the contrast to enter gradually. The use of the AP projection alone is considered sufficient, as it provides adequate diagnostic information for radiologists while also accommodating the patient’s condition.Conclusion: At the Radiology Department of UNS Hospital, Micturating Cystourethrography is conducted using two projections, namely AP plain film and AP post-contrast, with contrast media administered via the drip infusion method to ensure gradual entry. The AP projection alone is sufficient to provide adequate diagnostic information while also allowing for adjustments based on the patient’s condition.